The Grammatical and Textual Equivalence in the English-Indonesian Translation of Milan’s the Duchess War - Afifah (English Education Journal, 2024)
This study examines grammatical and textual equivalence in the translation of Courtney Milan's novel “The Duchess War” from English into Indonesian. The data were collected through qualitative content analysis of selected dialogs from the original text and their translations, using the categories of grammatical equivalence (such as number, gender, person, tense, aspect, and voice) and textual equivalence (such as reference, substitution, ellipsis, conjunction, and lexical cohesion). The data were analyzed using Baker's (1992) theory of equivalence and Halliday and Hasan's (1976) theory of cohesive devices, with triangulation of methods to ensure the validity of the findings. The findings of this study show a high level of equivalence, with 89.7% grammatical equivalence and 88.7% textual equivalence. Although there were some cases of misalignment, the overall translation accuracy remained high. The main contribution of this study is to provide insights for translators regarding the importance of considering cultural context in achieving accurate and cohesive translations. This study implies that grammatical and textual equivalence is not enough to guarantee translation accuracy. Thus, paying attention to the cultural nuances will also help translators to effectively convey the intended meaning of source language in cross-cultural communication context.